Expertise-dependent perceptual performance in chess tasks with varying complexity - Küchelmann, Thomas; Velentzas, Konstantinos; Essig, Kai; Koester, Dirk; Schack, Thomas (Frontiers in Psychology, 2022)
Perceptual performance, anticipating opponents' strategies, and judging chess positions especially in subliminal processing is related to expertise level and dependent on chunking processes. It becomes obvious that chess expertise is a multidimensional phenomenon related predominantly to experience. Under consideration of chess expertise categorization, we conducted two priming experiments expanding existing designs by gradually increasing the target and task complexity. The main aim was the evaluation of potential visuocognitive limitations. The results reveal experts' perceptual superiority manifested by their faster reaction times in settings with increased stimulus and task complexity. Further, experts' priming effects seem to be affected by the target content and/ or priming duration. For short prime duration, experts show priming effects only for less complex prime-target content. Interestingly, for longer prime duration and more complex prime-target content, all participants reveal priming effects. In summary, we argue that experts' visuocognitive processing (i.e., detecting or anticipating potential threats to the king) is rooted in a more efficient visuocognition due to stored chunks of checking and mating constellations. We suggest that visuocognitive limitations are related also to the prime-target complexity as well as to the task. Further investigations must be conducted in order to elucidate the factors with an increased impact on chess players' performance.